NILAI-NILAI PENDIDIKAN ISLAM DALAM SERIAL ANIMASI HAFIZ HAFIZAH DAN RELEVANSINYA PADA MATERI PAI KELAS V SD - Savina Aulia Azzahra; Sokhibul Arifin; Ika Puspitasari (Jurnal Muara Pendidikan, 2023)
This study aims to determine the values of Islamic religious education in the animated film series Hafiz Hafizah and to relate them to Islamic education material for grade V SD. This study uses qualitative methods and the type of research is Library research by randomly selecting 5 episodes by the researcher. The results of this study indicate that the values of Islamic religious education in this film are as follows: 1) having faith in the Apostle by behaving tabligh in the episode "Bazaar for Goodness part 1" is relevant to the material of chapter 3 Faith in the apostles of Allah SWT. 2) having faith in Allah's book in the episode "I want to know part 2" is relevant to the material in chapter 4 Faith in Allah's books. 3) Pray in the episode "Hafiz hiccups part 2" relevant to the material for chapter 2 Asma'ul Husna. 4) Sincerity in the episode "Let's go to Mecca part 2" is relevant to the material in chapter 6 respecting opinions, simplicity, and sincerity. 5) Please help in the episode "Greed is a problem part 1" relevant to the material in chapter 1 of At-tin and Al-ma'un letters.